2014
DOI: 10.3390/ijerph110807820
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Risks and Pregnancy and Infant Health Outcomes in Florida Farmworkers

Abstract: The agricultural industry has some of the highest incidence rates and numbers of occupational injuries and illnesses in the United States. Injuries and illnesses in agriculture result from accidents, falls, excessive heat, repetitive motion and adverse pesticide exposure. Women working in agriculture are exposed to the same hazards and risks as their male counterparts, but can face additional adverse impacts on their reproductive health. Yet, few occupational risk assessment studies have considered the reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
1
15
1
Order By: Relevance
“…The findings from our study revealed that pregnant women daily labourers and farmers are particularly at risk for illnesses during pregnancy. This finding is similar to that reported in a study in which heavy workloads during pregnancy, including long workdays, are associated with illnesses [44]. Those households with higher annual household expenditures are also at risk of catastrophic payments during illnesses [45].…”
Section: Discussionsupporting
confidence: 87%
“…The findings from our study revealed that pregnant women daily labourers and farmers are particularly at risk for illnesses during pregnancy. This finding is similar to that reported in a study in which heavy workloads during pregnancy, including long workdays, are associated with illnesses [44]. Those households with higher annual household expenditures are also at risk of catastrophic payments during illnesses [45].…”
Section: Discussionsupporting
confidence: 87%
“…A study of 260 farmworker mothers observed that all of them worked during pregnancy either entirely, or partially and have stopped working at week 22.8 ± 7.9 (mean, sd). They also reported that~52% of the fathers worked in agriculture during pregnancy [34]. Twelve studies assessed respiratory effects considering prenatal exposure to pesticides, with only two of them focusing exclusively on prenatal exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Prenatal exposure to pesticides (OP and pyrethroids) was shown to increase the risk of early cough, wheeze, and IgE production [22], and maternal postnatal occupational exposure to biocides/fungicides increased the likelihood of childhood wheeze [39]. Moreover, mothers working in ferneries were 2.7 times more likely to report a child's diagnosis of a respiratory condition, compared to nursery farm workers [34]. While nursery farm workers are less exposed due to the lower height of the exposure, those working at ferneries apply pesticides at the same level as their breathing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several components of physical and mental health among farmworker family members are particularly related to their housing conditions. 81 These include respiratory health, 82,83 dermatological health, 84,85 injuries and trauma; infectious diseases, such as tuberculosis, hepatitis, sexually transmitted diseases, and HIV, 86 parasites, 87 the neurobehavioral development of children, 88 and sleep quality. 89 Components of mental health affected by housing conditions include stress, anxiety, depression, and alcohol dependence 39,90 as well as interpersonal conflict, domestic violence, and sexual assault.…”
Section: Topicsmentioning
confidence: 99%